Exponential Attractor for Lattice System of Nonlinear Boussinesq Equation - Min Zhao; Shengfan Zhou (Discrete Dynamics in Nature and Society)
We study the lattice dynamical system of a nonlinear Boussinesq equation. We first verify the Lipschitz continuity of the continuous semigroup associated with the system. Then, we provide an estimation of the tail of the difference between two solutions of the system. Finally, we obtain the existence of an exponential attractor of the system.